The Clinical Efficacy of Multi-strain Probiotics in the Management of Acute Watery Diarrhoea of Children aged 2 Months to 5 Years-a Randomized Controlled Trial (Bangladesh Journal of Child Health, 2019)
Background: Acute gastroenteritis is considered as one of the most common causes of under-five morbidity and mortality worldwide. Standard treatment is the use of oral rehydration solution (ORS), intravenous fluid if indicated, and zinc supplement. Recently, the use of probiotics has been introduced as an adjunct to the treatment of acute gastroenteritis. The aim of this study is to determine the clinical efficacy of multi-strain probiotics as adjunct treatment of acute gastroenteritis.Methodology: A randomized controlled trial was done in 250 bed district Sadar Hospital, Brahmanbaria, Bangladesh from January 2016 to June 2017. After fulfilling the inclusion criteria, 507 children aged 2 months to 5 years were enrolled in this study. Those with dysentery, chronic diarrhea, diarrhea due to known genetic disorder, chronic illness, malnutrition, systemic infection, CNS disorder and congenital malformation were excluded. Children were divided into two groups randomly. One group was With Probiotic, zinc and standard WHO (ORS) as case and other group was Without Probiotic, zinc and standard WHO ORS as control.Results: Among 507 children, 257 were without probiotic while 250 were with probiotic. The mean difference in stool frequency between the two groups were 3.3 after 24 hours, 3.5 after 48 hours and 1.6 after 72 hours after hospitalization which was statistically significant (p=0.000). Reduction of stool frequency was highest after 48 hours of admission. Mean duration of hospital stay was 4.40±1.22 days in control and 4.03±.89 days in case group. Probiotic group children with exclusive breastfeeding had mean recovery time of 3.95±0.85 days and those who were not exclusively breastfeed had recovery time of 4.2±0.95 days (p=0.025).Conclusion: Probiotic is efficacious in reducing purging duration and frequency of acute watery diarrhea in children.Bangladesh J Child Health 2019; VOL 43 (2) :97-101